2007
DOI: 10.1007/s11090-007-9100-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Fine Particles with a SnO2 Film by Using a Polyhedral-Barrel Sputtering System

Abstract: Fine particles were modified with a thin film of SnO 2 by using a barrel sputtering system that is a dry process. The conditions for the preparation of SnO 2 were studied by reactive sputtering onto a glass plate substrate. The optimal conditions for the preparation of tetragonal SnO 2 were identified as 60% partial oxygen pressure and 1.0 Pa total gas pressure with the substrate at room temperature. Under the optimized conditions, the surfaces of Al flake particles were modified with a thin film of SnO 2 . XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…In a separate experiment using this technique, the thickness of the layer on the particles was approximately 1/6 to 1/10th of the thickness of the film on a glass plate for the same preparation time. 7) The thickness of the TiN layer on the Al flakes was almost the same as that obtained in the separate experiment. Consequently, it was revealed that the entire surface of each Al flake was uniformly coated with a TiN layer by using the barrel-sputtering system.…”
Section: Surface Coatings Of Powdery Materialssupporting
confidence: 76%
See 1 more Smart Citation
“…In a separate experiment using this technique, the thickness of the layer on the particles was approximately 1/6 to 1/10th of the thickness of the film on a glass plate for the same preparation time. 7) The thickness of the TiN layer on the Al flakes was almost the same as that obtained in the separate experiment. Consequently, it was revealed that the entire surface of each Al flake was uniformly coated with a TiN layer by using the barrel-sputtering system.…”
Section: Surface Coatings Of Powdery Materialssupporting
confidence: 76%
“…5-7) These coated particles can be used in several applications, for example, they can be used in hydrogen storage materials with high durability in air, 1) electrochemical catalysts, 2) and paint pigments. 7) Transition metal nitride films have interesting properties such as a high melting point, extreme hardness, and excellent thermal and chemical inertness, which make them useful materials in the industry. Titanium nitride (TiN), in particular, is one of the most successful materials for industrial applications such as coatings for high-speed steel cutting tools, diffusion barriers in semiconductors, and coatings for decorative.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of nanostructures on particle surfaces is a vital step in the preparation of functionalized powdery materials. [1][2][3][4][5][6] Consequently, our group has previously developed new methods that allow the uniform deposition of thin films [7][8][9][10][11][12][13] on particles. We refer to these processes as the polygonal barrel-sputtering system [7][8][9][10][11][12] and the polygonal barrel-plasma chemical vapor deposition (PCVD) system.…”
Section: Introductionmentioning
confidence: 99%
“…The AC power for sputtering was supplied by RF power generation (13.56 MHz). Samples were prepared following reported procedures [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. NaCl powder (particle size: 250 -500 μm, Kanto Chemical or The Salt Industry Center of Japan) was introduced into a hexagonal barrel and then the barrel was placed in a vacuum chamber.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…Based on this background, we developed a novel surface modification method for powders using the sputtering technique, which we call the "polygonal barrel-sputtering method" [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The polygonal barrel-sputtering method has been successfully used for uniform surface modification of particles composed of metals [17], alloys [18], metal oxides [19][20][21][22][23][24], polymers [25][26][27], and carbon [28][29][30][31][32]. In this study, the surfaces of NaCl particles were modified with metal films using the polygonal barrel-sputtering method to demonstrate the application of our method to the surface modification of water-soluble and water-reactive powders.…”
Section: Introductionmentioning
confidence: 99%